Is transcranial direct current stimulation beneficial for treating pain, depression, and anxiety symptoms in patients with chronic pain? A systematic review and meta-analysis - Wen, Yu-Rong; Shi, Jian; Hu, Zheng-Yu; Lin, Yang-Yang; Lin, You-Tian; Jiang, Xue; Wang, Rui; Wang, Xue-Qiang; Wang, Yu-Ling (Frontiers in Molecular Neuroscience, 2022)
Background: Transcranial direct current stimulation (tDCS) has shown uncertain therapeutic effects for treatment of chronic pain, depressive or anxiety symptoms. Objectives: To ascertains the treatment effect of tDCS on patients suffering from chronic pain, depressive or anxiety symptoms and potential factors that modulate the effectiveness of tDCS. Methods: Literature search was performed on PubMed, Embase, Web of Science and Cochrane Library from inception to July 2022. Randomized controlled trials that reported the effects of tDCS on pain and depression or anxiety symptoms in patients with chronic pain were included. Results: Twenty-two studies were included in this review. Overall pooled results indicated that the use of tDCS can effectively alleviate short-term pain intensity (standard mean difference [SMD]: −0.43, 95% confidence interval [CI]: −0.75 to −0.12, P = 0.007) and depressive symptoms (SMD: −0.31, 95%CI, −0.47 to −0.14, P < 0.001), middle-term depressive symptoms (SMD: −0.35, 95% CI: −0.58 to −0.11, P = 0.004), long-term depressive symptoms (ES: −0.38, 95% CI: −0.64 to −0.13, P = 0.003) and anxiety symptoms (SMD: −0.26, 95% CI: −0.51 to −0.02, P = 0.03) compared with the control group. Conclusion: tDCS may be an effective treatment for patients with chronic pain and may experience anxiety or depression in the short term. Stimulation site, stimulation frequency and pain conditions were potential influencing factors for the therapeutic effect of tDCS.